2019
DOI: 10.3390/pr7070471
|View full text |Cite
|
Sign up to set email alerts
|

Choline-Based Ionic Liquids as Media for the Growth of Saccharomyces cerevisiae

Abstract: Ionic liquids (ILs) have garnered great attention as alternative solvents in many biological reactions and applications. However, its unknown toxicity is in line with the challenges to use it for biological applications. In this study, three choline based Ionic Liquids—choline saccharinate (CS), choline dihydrogen phosphate (CDHP), and choline tryptophanate (CT) were assessed for their suitability on the growth of Saccharomyces cerevisiae. The ILs were incorporated into the growth media of S. cerevisiae (defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…After the first melting of [Chol]­[H 2 PO 4 ], the sample did not show a tendency to crystallize but exhibited a glass transition at 245 K in fair agreement with the previously reported T g = 248.6 K . However, slow decomposition of the sample was detected right above T crI‑l = 457 ± 2 when DSC was used, instead of as high as at 503 K during thermogravimetric experiments .…”
Section: Results and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…After the first melting of [Chol]­[H 2 PO 4 ], the sample did not show a tendency to crystallize but exhibited a glass transition at 245 K in fair agreement with the previously reported T g = 248.6 K . However, slow decomposition of the sample was detected right above T crI‑l = 457 ± 2 when DSC was used, instead of as high as at 503 K during thermogravimetric experiments .…”
Section: Results and Discussionsupporting
confidence: 89%
“…31 In an earlier study, 32 the crII−crI transition was mistaken for melting, and the low corresponding enthalpy was assigned to the plastic character of the crII phase. According to Rana et al, 31 After the first melting of [Chol][H 2 PO 4 ], the sample did not show a tendency to crystallize but exhibited a glass transition at 245 K in fair agreement with the previously reported T g = 248.6 K. 36 However, slow decomposition of the sample was detected right above T crI-l = 457 ± 2 when DSC was used, instead of as high as at 503 K during thermogravimetric experiments. 36 Thus, the T g values might be offset due to the low purity of the melted sample.…”
Section: And [Leu][no 3 ]supporting
confidence: 80%
See 1 more Smart Citation
“…Non-nutritive sweeteners and carboxylic acids were reported as anionic portions. 71,72 Sivapragasam et al 71 reported biological applications of choline-based ILs (choline saccharinate, choline dihydrogen phosphate, and choline tryptophanate) for the growth of Saccharomyces cerevisiae . The ILs composed of a non-nutritive sweetener (choline saccharinate) and choline dihydrogen phosphate contributed to the rapid growth of the microorganism according to the rate of glucose consumption, highlighting the biocompatibility of ILs.…”
Section: Ils With Improved Biocompatibilitymentioning
confidence: 99%
“…Thus the thermal stability of lysozyme can be increased (Su and Klibanov, 2015), the catalytic activity of catalase (Harifi-Mood et al, 2017), laccase (Khodaverdian et al, 2018) and lipase (Nascimento et al, 2019) was conserved and the biotransformation of steroids by bacteria was efficient (Mao et al, 2019). Finally, Sivapragasam et al have shown that some choline-based ionic liquids promoted the growth of the yeast Saccharomyces cerevisiae, suggesting that deep eutectic solvents could act as an alternative medium for microbial cultures (Sivapragasam et al, 2019).…”
Section: 7applications In Formulation For Drug Delivery and Biotechnologymentioning
confidence: 99%